Susceptibility to chlorhexidine and mupirocin among methicillin-resistant Staphylococcus aureus clinical isolates from a teaching hospital - Taniela Marli Bes; Lauro Perdigão-Neto; Roberta Ruedas Martins; Inneke Heijden; Priscila de Arruda Trindade; Gaspar Camilo; Debora Satie Nagano; Diego Mongelos; Ana Paula Marchi; Mariama Tomaz; Larissa Marques de Oliveira; Flavia Rossi; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2021)
ABSTRACT Despite the widespread use of chlorhexidine (CHX) to prevent infection, data regarding the in vitro action of CHX against methicillin-resistant Staphylococcus aureus (MRSA) are limited. Clinical isolates from Hospital das Clinicas, Sao Paulo, Brazil, identified during 2002/2003 and 2012/2013 were studied to describe the susceptibility to CHX and mupirocin, molecular characteristics, and virulence profile of MRSA. Susceptibility test to Mupirocin was performed by the disk diffusion method and to CHX by the agar dilution technique. PCR for virulence genes, mecA gene and Staphylococcal Cassette Chromosome mec (SCCmec) types were investigated as well. Mupirocin- and CHX-resistant isolates were sequenced using the IlluminaTM plataform. Two hundred and sixteen MRSA clinical isolates were evaluated: 154 from infected and 62 from colonized patients. Resistance to mupirocin was observed in four isolates assigned as SCCmec type III and STs (ST05; ST239 and ST105) carrying mupA and blaZ, two of them co-harboring the ileS gene. Only one isolate assigned as SCCmec type III was resistant to CHX (MIC of 8.0 μg.mL-1) and harbored the qacA gene. Resistance to chlorhexidine and mupirocin were found in isolates carrying qacA and mupA in our hospital. Since these genes are plasmid-mediated, this finding draws attention to the potential spread of resistance to mupirocin in our hospital.